Significantly suppressed coalescence in flowing polymer blends by a synergy between surface chemistry and roughness of nanoparticles. (3rd May 2021) - Yao, Yingchun; Xiang, Siying; Lu, Miaomiao; Huang, Yajiang; Kong, Miqiu; Li, Guangxian
Abstract: The compatibilization efficiency of nanoparticles (NPs) towards immiscible polymer blends highly depends on the structural details of NPs. Here, we synthesized three kinds of fluorescently labeled silica NPs with different surface chemistries and roughnesses by using the sol-gel and electrostatic adsorption methods. The efficiencies of NPs in stabilizing immiscible polyisobutylene/polyethylene oxide (10/90) blends under slow shear flow were evaluated in-situ by using the flow-confocal laser scanning microscopy. It was found that the surface chemistry and concentration of NPs determined whether the NP-laden blends get refined or coarsened while the particle roughness further regulates the magnitude of the change in the phase size. Hydrophobic NPs with nanoscale roughness demonstrated the highest stabilization efficiency owing to better dispersion at the blend interface. Therefore, surface roughness is a promising parameter in rationally designing NP-based compatibilizers for polymer blends. Graphical abstract: Image 1 Highlights: Rough silica NPs were synthesized by using the electrostatic adsorption method. Interfacially located hydrophobic NPs could efficiently stabilize the flowing blend. Hydrophobic rough NPs have the highest stabilization effect due to better dispersion. Roughness is an important parameter determining the compatibilization efficiency.